Charge-tagged polar phosphine ligands in Pd-catalysed reactions in aqueous and ionic media. Issue 10 (7th March 2018) - van Zyl, Vivien L.; Muller, Alfred; Williams, D. Bradley G.
Graphical abstract: Highlights: Imidazolium and phosphate-tagged phosphine ligands synthesised in good yields. Charge-tagged ligands form active catalysts for Heck and Suzuki reactions. Reactions are possible in aqueous and ionic media. The catalyst is recyclable without loss of activity. Abstract: A new range of polar imidazolium and phosphate-containing ligands was synthesised from readily available starting materials in high yielding multi-step transformations. These ligands were used to generate Pd catalysts for Suzuki and Heck C–C coupling reactions in organic and organic/aqueous media. The catalysts performed well in aqueous media in the Suzuki reaction and less well in the Heck reaction, related to substrate solubility in the aqueous media. When moving to ionic liquids, the Heck reaction dramatically improved, especially in media compatible with the polar catalysts and the non-polar reagents. In all cases, the catalysts were stable to the formation of Pd black, a form of degradation that frequently befalls Pd catalysts. The catalysts could be successfully recycled without loss of activity.